A urea-modified tryptophan based in situ reducing and stabilizing agent for the fabrication of gold nanoparticles as a Suzuki–Miyaura cross-coupling catalyst in water. Issue 4 (22nd January 2019) - Sasmal, Supriya; Debnath, Mintu; Nandi, Sujay Kumar; Haldar, Debasish
Abstract : Urea modified tryptophan has been used as an in situ reducing and stabilizing agent for the fabrication of gold nanoparticles and the gold nanoparticles efficiently catalyzed the Suzuki–Miyaura cross-coupling reaction in water. Abstract : Urea-modified tryptophan has been used as an in situ reducing and stabilizing agent for the fabrication of gold nanoparticles in water. The tryptophan side chain NH has been used for the reduction of gold ions in HAuCl4 to metallic gold and carboxylic acid functionality helps to stabilize the gold nanoparticles. This was confirmed by a controlled reaction with urea-modified leucine which failed to form any gold nanoparticles. The resultant gold nanoparticles have been characterized by various spectroscopic techniques such as UV-visible spectroscopy, FT-IR spectroscopy and microscopic techniques such as FE-SEM and TEM. Moreover, we have shown that the urea-modified tryptophan stabilized gold nanoparticles catalyze the Suzuki–Miyaura cross-coupling reaction. The gold nanoparticle catalyzed Suzuki–Miyaura cross-coupling reaction between 4-bromobenzoic acid and phenylboronic acid in water provides 92% yield in 40 minutes. The high efficiency exhibited by the gold nanoparticle catalyst was effectively translated to a large number of Suzuki–Miyaura reactions between halides with phenylboronic acid. The results may inspire further research on gold nanoparticles catalysis in water.